Nutritional and nutraceutical composition of Pansies (Viola × wittrockiana) during flowering - Fernandes, Luana (2018)
Edible flowers consumption and use are an increasing food trend worldwide, although information concerning their nutritional composition and nutraceutical value is still scarce. Thus, the aim of this study was to contribute to the popularization of pansies (Viola × wittrockiana), through the analysis of the nutritional and nutraceutical features of pansies with different colors (white, yellow, and red) and flowering stages. Both flower type and flowering stage influenced the flower composition. When completely open, white and yellow pansies had the highest contents of protein (>2.00 g/100 g fresh weight), while red pansies had the highest content of carbohydrates (8.0 g/100 g fresh weight). Regarding the fatty acid profiles, linoleic acid was always predominant (ranging between 18.7 and 51.0 g/100 g fatty acids), followed by the palmitic and linolenic acids. During flowering, there was an increase in protein, fat, and linolenic acid contents in white and yellow pansies, whereas in red pansies the values did not change. Red pansies were characterized by the highest contents of total carotenoids (873 to 1300 μg β-carotene/g dry weight) and monomeric anthocyanins (303 to 402 μg Cy-3 glu/g dry weight); however, white and yellow pansies showed an increase in the values of total reducing capacity (total phenols), hydrolysable tannins, flavonoids, monomeric anthocyanins, and antioxidant activity from the bud to completely open flower stage. Our results underline the nutritional differences between pansies with different colors at distinct stages of development and their potential health benefits, suggesting that they can be used as ingredient to improve the nutritional properties of foods.